Slang dalam Bahasa Indonesia: Kajian Morfosemantik - M. Bahri Arifin; Asnan Hefni; Purwanti Purwanti (Universitas Mulawarman, 2022)
Slang is one of language varieties used by a speaker in an informal communication event for specific purposes. It is used for the purpose of effective communication among a group of speakers; however it can also trigger a communication failure. Slang usage results in effective and fluent communication if speakers and hearers have familiarity and comprehension towards form and meaning of slang utterances, and vice versa. This study is aimed at describing the analysis result of Indonesian slang utterances based on morphological aspects and semantics which cover morphological process of slang word formation and types of slang meanings. The design of this study was qualitative approach with descriptive analysis method. The data were obtained from the recording technique/the inventory of Indonesian slang utterances. The list of slang utterances was comprised of familiar utterances and those used by Indonesian speakers during face-to-face or virtual interaction. Based on the analysis, Indonesian slang words were formed by morphological process and phonological structure change. Through morphological process, Indonesian slang word was formed by abbreviating first syllable in the first word and it is in the form of abbreviation. In addition, slang word formation through phonological structure change covered complete word reversal, syllable reversal, and vocal replacement. The meanings of Indonesian slang words were lexical, denotative, conceptual and connotative.